Synthesis of Tin(II) Oxide (SnO) Nanoparticle by Hydrothermal Method - Saddam Husein; Endang Tri Wahyuni; Mudasir Mudasir (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
This study aims to prepare nanomaterial tin(II) oxide (SnO) by using a simple hydrothermal method at low temperatures. The precursors used were tin(II) chloride dihydrate and sodium hydroxide pellets. Solid tin(II) chloride dihydrate and natrium hydroxide pellets are firstly dissolved in ethanol solvents separately and stirred for 3 h for each solution at a constant temperature 26oC. Characterization in this study were carried out by using X-ray diffraction (XRD) and Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDX). The results of the XRD analysis shows that the sample of SnO nanoparticle is in accordance with the standard JCPDS SnO structure. SnO nanoparticle has tetragonal crystal structures and PSC: tp4 groups. It can be concluded that the tetragonal SnO nanostructure can be produced by a simple hydrothermal method at low temperatures by optimizing several synthesis parameters. The structure of SnO nanostructure has several potential applications i.e the absorption of heavy metals, optics, and as a catalyst for dye photodegradation.